If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 28 + -1(2c + 3) = 2(c + 5) + 5 Reorder the terms: 28 + -1(3 + 2c) = 2(c + 5) + 5 28 + (3 * -1 + 2c * -1) = 2(c + 5) + 5 28 + (-3 + -2c) = 2(c + 5) + 5 Combine like terms: 28 + -3 = 25 25 + -2c = 2(c + 5) + 5 Reorder the terms: 25 + -2c = 2(5 + c) + 5 25 + -2c = (5 * 2 + c * 2) + 5 25 + -2c = (10 + 2c) + 5 Reorder the terms: 25 + -2c = 10 + 5 + 2c Combine like terms: 10 + 5 = 15 25 + -2c = 15 + 2c Solving 25 + -2c = 15 + 2c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-2c' to each side of the equation. 25 + -2c + -2c = 15 + 2c + -2c Combine like terms: -2c + -2c = -4c 25 + -4c = 15 + 2c + -2c Combine like terms: 2c + -2c = 0 25 + -4c = 15 + 0 25 + -4c = 15 Add '-25' to each side of the equation. 25 + -25 + -4c = 15 + -25 Combine like terms: 25 + -25 = 0 0 + -4c = 15 + -25 -4c = 15 + -25 Combine like terms: 15 + -25 = -10 -4c = -10 Divide each side by '-4'. c = 2.5 Simplifying c = 2.5
| A-4*a-6= | | -9-x=12-4x | | x^4+2x^3-3x^2-8x-4=0 | | 5-4x=-3(-2-2x) | | 6+7x=6x+0 | | (4/5x-3)2= | | 5x/12-1/4=1/6 | | m+8=-19 | | (5x)x(5x)= | | 7-2x=2x-41 | | 7w-3w+4w= | | -6x-8=2x+0 | | 1.04(1.25)(6-x)=7 | | x+(x+5)+3x=90 | | 1x+(-1)y+(1)=0 | | -3-(-3)=-2(4-4) | | 2+4+6=128 | | 1x+(1)y+(1)=0 | | n(x-y)+(n-9)(y-x)=0 | | x-(5x-1)=3x+(-x+2) | | 2x+5=3x+17 | | 6-x=2X-21 | | -3(y+8)=-2y-9 | | 7x+3=15+3x | | 10(-12y+18)-22(x-10)8y= | | 99*4= | | 2x+2-7=0 | | 24x^2=384 | | 25+2x=37 | | 8x+(-8x-4)=4 | | 6senx=0 | | 2senx=-2 |